What Makes Growth Sustained? - Ostry, Jonathan (IMF Working Papers; Working Paper ;, 2008)
We identify structural breaks in economic growth in 140 countries and use these to define "growth spells:" periods of high growth preceded by an upbreak and ending either with a downbreak or with the end of the sample. Growth spells tend to be shorter in African and Latin American countries than elsewhere. We find that growth duration is positively related to: the degree of equality of the income distribution; democratic institutions; export orientation (with higher propensities to export manufactures, greater openness to FDI, and avoidance of exchange rate overvaluation favorable for duration); and macroeconomic stability (with even moderate instability curtailing growth duration).